Rapid Nestling Mortality in Arctic Peregrine Falcons due to the Biting Effects of Black Flies - Franke, Alastair; Lamarre, Vincent; Hedlin, Erik (ARCTIC, 2016)
This note describes nestling mortality in Arctic Peregrine Falcons (Falco peregrinus tundrius) due to the biting effects of blood-feeding black flies (Diptera: Simuliidae). At a nest site near Rankin Inlet, Nunavut, Canada (62˚49′ N, 92˚05′ W), a brood of four nestlings died on 20 July 2013 from the direct effects of severe bites attributed to black flies. Within three hours of the onset of blood-feeding, black flies had caused widespread, uniformly distributed hemorrhagic coalescent lesions over the head and body of all nestlings. Approximately seven hours after the first flies appeared, the female falcon removed the carcasses of the dead nestlings from the nest. Nestlings at eight additional sites also suffered the effects of biting black flies in 2013, resulting in the deaths of 13 of 35 nestlings. A less pronounced outbreak also occurred in 2012 and resulted in the deaths of seven nestlings at four sites. No nestling mortality due to black flies has been documented in any other year from 1982 through 2015. To our knowledge, these observations document the northernmost lethal attack by ornithophilic black flies in North America. Cet article décrit des événements de mortalité d’oisillons chez le faucon pèlerin (Falco peregrinus tundrius) causés par des morsures de mouches noires hématophages (Diptera : Simuliidae). À un site de nidification près de Rankin Inlet, Nunavut, Canada (62˚49′ N, 92˚05′ O), les quatre oisillons d’une couvée sont morts le 20 juillet 2013 des effets directs de morsures sévères attribuables aux mouches noires. Dans les trois heures suivant le début de l’activité des hématophages, les mouches noires avaient causé des lésions hémorragiques et coalescentes uniformément distribuées sur la tête et le corps des oisillons. Environ sept heures après l’apparition des premières mouches, la femelle a retiré les carcasses des oisillons morts du nid. Des oisillons à huit autres sites de nidification ont également subi les effets des mouches noires hématophages en 2013, entraînant la mortalité de 13 ...